Commitment and investments in homosexual and heterosexual romantic relationships - Rodrigues, D. (2018)
Framed by the Investment Model (Rusbult, 1980, 1983), the maintenance of romantic relationships are inﬂuenced by the experience of general commitment and the perceived investments applied in the relationship. Albeit showing the robustness of these predictions among heterosexual romantic relationships, literature suggests homosexual romantic relationships to be socially and legally marginalized, characterized by lower investments and general commitment. To better understand the dynamics underlying heterosexual and homosexual romantic relationships, we suggest the importance of additionally considering the moral obligations to remain in the relationship (i.e., moral commitment; Johnson, 1991). As such, we conducted a correlational study to explore the impact of cohabitation in individuals’ experiences of (general and moral) commitment and investments. Results show that, for homosexual relationships, cohabitation increases the experience of general commitment and investments, while no differences emerged in heterosexuals. Furthermore, homosexuals (vs. heterosexuals) reported a higher level of moral commitment. We discuss these results under our framework and the need to take into account norms and changes in society.